Calibrating Functional Parameters in the Ion Channel Models of Cardiac Cells. Issue 514 (2nd April 2016) - Plumlee, Matthew; Joseph, V. Roshan; Yang, Hui
ABSTRACT: Computational modeling is a popular tool to understand a diverse set of complex systems. The output from a computational model depends on a set of parameters that are unknown to the designer, but a modeler can estimate them by collecting physical data. In the described study of the ion channels of ventricular myocytes, the parameter of interest is a function as opposed to a scalar or a set of scalars. This article develops a new modeling strategy to nonparametrically study the functional parameter using Bayesian inference with Gaussian process prior distributions. A new sampling scheme is devised to address this unique problem.